Low band-gap polymers incorporating benzotriazole and 5,6-dialkoxy-benzothiadiazole as solution processable electrochromic materials - W. T. Neo; Q. Ye; X. Wang; H. Yan; J. Xu (eXPRESS Polymer Letters)
Two series of donor-acceptor type conjugated polymers bearing benzotriazole or 5,6-dialkoxy-benzothiadiazole as acceptors unit are synthesized via Stille coupling. The optical, electrochemical, spectroelectrochemical characterizations and theoretical calculations are carried out. The polymers display excellent solubility in common organic solvents upon the introduction of long aliphatic side chains. The electrochromic performances of the polymers are also studied. Upon oxidation, the polymers switch from magenta or blue to a transmissive light blue state. In particular, respectable optical contrasts of about 44 and 40% are obtained in the visible and near infrared (NIR) region respectively for P2. The polymers also reveal fast switching of about from one second to a few seconds. In addition, P2 exhibits a high coloration efficiency of 518 and 561 cm2/C in the visible and NIR region respectively. The promising electrochromic behaviour of these polymers, together with the enhanced solubility will allow large-scale processing and advancement towards real applications.